เชื้อก่อโรคในผู้ป่วยภาวะท่อน้ำตาอุดตันแบบปฐมภูมิที่เข้ารับการรักษา ด้วยการผ่าตัดเปิดทางเชื่อมระหว่างถุงน้ำตาและโพรงจมูกในโรงพยาบาลอุทัยธานี Pathogen of Primary Acquired Nasolacrimal Duct Obstruction underwent External Dacryocystorhinostomy in Uthai Thani Hospital - Benchatikul, Thitta (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2019)
บทคัดย่อ วัตถุประสงค์ : เพื่อศึกษาเชื้อก่อโรคในผู้ป่วยภาวะท่อน้ำตาอุดตันแบบปฐมภูมิที่เข้ารับการรักษาด้วยการผ่าตัดเปิดทางเชื่อมระหว่างถุงน้ำตาและโพรงจมูกในโรงพยาบาลอุทัยธานี สถานที่ศึกษา : แผนกจักษุกลุ่มงานจักษุวิทยา โรงพยาบาลอุทัยธานี รูปแบบการวิจัย : เชิงพรรณนาแบบย้อนหลัง (retrospective descriptive study) กลุ่มตัวอย่าง : ผู้ป่วยที่ได้รับการวินิจฉัยว่ามีภาวะท่อน้ำตาอุดตันแบบปฐมภูมิและเข้ารับการผ่าตัดเปิดทางเชื่อมระหว่างถุงน้ำตาและโพรงจมูกในช่วงเวลาตั้งแต่วันที่ 1 มกราคม 2560 ถึง 31 ธันวาคม 2561 จำนวน 44 ตา วิธีการศึกษา : เก็บข้อมูลจากเวชระเบียนผู้ป่วยโรงพยาบาลอุทัยธานี รายงานข้อมูลเป็นจำนวนและร้อยละ ผลการศึกษา : ผลการเพาะเชื้อจากสิ่งส่งตรวจที่เก็บระหว่างผ่าตัด พบผลการเพาะเชื้อเป็นบวก 28 ตา จากทั้งหมด 44 ตา คิดเป็น ร้อยละ 63.6 เชื้อส่วนใหญ่ที่พบเป็นแบคทีเรียกรัมลบ16ตา คิดเป็นร้อยละ57.1 ที่พบมากที่สุด คือ เชื้อ Pseudomonas aeruginosa ร้อยละ 42.9นอกจากนี้ยังพบเชื้อแบคทีเรียกรัมบวก 12 ตา คิดเป็นร้อยละ 42.9 ที่พบมากที่สุด คือ เชื้อCoagulase-negative staphylococci ร้อยละ 25.0 โดยส่วนใหญ่กลุ่มผู้ป่วยที่มีผลการเพาะเชื้อเป็นบวก คือ กลุ่มผู้ป่วยภาวะท่อน้ำตาอุดตันแบบชนิดเรื้อรังทั้งหมด สำหรับผลการตรวจความไวต่อยาปฏิชีวนะพบว่า เชื้อที่พบส่วนใหญ่ตอบสนองได้ดีต่อยาปฏิชีวนะกลุ่ม Ciprofloxacin สรุป : ผู้ป่วยภาวะท่อน้ำตาอุดตันแบบปฐมภูมิในโรงพยาบาลอุทัยธานีที่เป็นกลุ่มที่มีอาการเรื้อรัง ส่วนใหญ่ตรวจพบมีการติดเชื้อ โดยเชื้อก่อโรคส่วนใหญ่เป็นเชื้อแบคทีเรียกรัมลบ ส่วนยาปฏิชีวนะที่พบว่าสามารถครอบคลุมเชื้อทั้งกลุ่มแบคทีเรียกรัมลบและกรัมบวกได้ดีที่สุด ได้แก่ ยา Ciprofloxacin คำสำคัญ : เชื้อก่อโรคถุงน้ำตาติดเชื้อภาวะท่อน้ำตาอุดตันการผ่าตัดเปิดทางเชื่อมระหว่างถุงน้ำตาและโพรงจมูก Abstract Background : Nasolacrimal duct obstruction is one of major risk factors leading to severe ocular infection, such as post-operative endophthalmitis. Previous studies showed it commonly encountered infection with various types of causative organism. Since 2017, Uthai Thani Hospital has provided external dacryocystorhinostomy surgery to treat patients with this condition. Thus, He objective is to study about the causative organism in this area to provide the baseline data and help in choosing appropriate treatment plan for this group of patients. Objective : To determine the microbiology and its antimicrobial susceptibilities in patients with primary acquired nasolacrimal duct obstruction who underwent external dacryocystorhinostomy. Setting : Ophthalmology department, Uthai Thani Hospital. Design : Retrospective descriptive study Subjects : 36 patients (44 eyes) with primary acquired nasolacrimal duct obstruction who underwent external dacryocystorhinostomy surgery in Uthai Thani Hospital during January 1st, 2017 to December 31st, 2018. Method : Medical records review was conducted to collect patient data, microbiological results and antimicrobial susceptibility results were collected. The categorical data were analyzed and reported as the number and percentages. Results : 28 of the 44 eyes (63.6%) were cultured positive. Most microorganisms were Gram-negative bacteria (16 samples or 57.1% of all positive culture samples), whereas Gram positive bacteria were found in 12 eyes (42.9%). The most frequently isolated microbial was Pseudomonas aeruginosa (42.9 %) followed by Coagulase-negative staphylococci(25%). All of the culture positive 28 eyes were patients with chronic dacryocystitis. Antimicrobial susceptibility testing demonstrated that ciprofloxacin was the most effective drug against all Gram-positive and Gram-negative organisms. Conclusion : Most of patients with primary acquired nasolacrimal duct obstruction, with chronic dacryocystitis, were cultured positive. Gram-negative organisms were frequently isolated.Ciprofloxacin was the most effective drug against all Gram-positive and Gram-negative organisms. Keywords : microbiology, dacryocystitis, acquired nasolacrimal duct obstruction, external dacryocystorhinostomy